Effects of forest residue mulching on organic matter and nutrient exports after wildfire in North-Central Portugal. - Prats, Sergio (2023)
The quick implementation of emergency stabilization measures is vital for minimizing post-fire soil erosion and the associated fertility loss. Mulching has proven to be highly effective in minimizing post-fire soil erosion, however few studies have investigated its impacts on organic matter (OM) and nutrient mobilization from burned forest areas. This study evaluates the effectiveness of forest residue mulching at reducing OM, N and P losses within the sed iments after a moderate-severity wildfire over a period of 5 years (Ermida, North-central Portugal). Untreated and mulched plots of ca. 100 m2 were bounded with geotextile fabric and sediments were collected from silt fences after a total of 29 periods. During the first five years after the fire, the accumulated OM, N and P exportations in the untreated plots were, respec tively, 199, 5.2 and 0.38 g m−2 ; and mulch significantly reduced these figures in, respectively, 91 %, 94 % and 95 % (p < 0.05). The overall OM content in the sediments of the untreated plots (45 %) was not different from the OM con tent of the mulched plots (34 %, p = 0.16). However, the N (8.9 g kg−1 ) and Pav contents (0.62 g kg−1 ) in the un treated plots were significantly higher than the N (5.6 g kg−1 ; p < 0.05) and Pav contents (0.36 g kg−1 ; p < 0.05) in the mulched plots. This effect was especially noticeable in the first year after fire. OM and TN contents in the sediments were highly variable throughout the study period, whereas Pav contents declined sharply in the first post-fire rainfall events, maintaining low values afterwards. The main factors driving nutrient exports were ash and litter cover, whereas no significant relationship was observed for OM exports. The present work has shown that forest residues ap plication can be a sustainable strategy for the conservation of soil carbon and nutrients in fire-affected areas.